nucleated red blood cells in cord blood of singleton term neonates and the risk factors affecting their count - AL-Dahwi, raja N.; Hassin, Riyadh A.; Salman, Gada A. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: